Perancangan Aplikasi Sistem Pakar Untuk Pengobatan Bekam Dengan Metode Dempster Shafer - Syahputra, Hadi (Jurnal Sains Informatika Terapan, 2023)
In the present time, to determine the cupping point, the clinic still uses the conventional method which takes a long time. One of the problems faced by the therapist is that they still have to open a book when they are facing a new cases while treating a patient. Which will hinder the treatment process. Thus, a computer based tool is needed that can help to obtain information about the cupping point. Expert Systems are a type of artificial intelligence that allows a computer to work in accordance with the thoughts of a subject matter expert in order to find a solution and solve a problem. The output of this expert system application is an application that aims to determine the cupping point using the Dempster Shafer method. The Dempster Shafer method for testing expert system applications begins with the owner's data entry of diseases, symptoms, and rules, after which the trapist can determine the cupping point for the patient based on the expert's thoughts, namely the owner himself.